2019
DOI: 10.1038/s41467-019-09207-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic control of tunable multi-state switching in ferroelectric thin films

Abstract: Deterministic creation of multiple ferroelectric states with intermediate values of polarization remains challenging due to the inherent bi-stability of ferroelectric switching. Here we show the ability to select any desired intermediate polarization value via control of the switching pathway in (111)-oriented PbZr0.2Ti0.8O3 films. Such switching phenomena are driven by kinetic control of the volume fraction of two geometrically different domain structures which are generated by two distinct switching pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
2
42
2
1
Order By: Relevance
“…The epitaxial orientation, as an alternative control parameter in heterostructure customization, has recently attracted rising interests for ferroelectric phase and domain design. [ 17–19 ] Several studies have revealed that the (111) orientation of a cubic substrate can introduce new types of phase instability and structure competition in a tetragonal ferroelectric via a dissimilar surface symmetry element, which we term epitaxial symmetry engineering. For example, unlike the commonly observed tetragonal phase in (001)‐oriented PbTiO 3 film, a SrTiO 3 (111) substrate tends to drive the polarization of overlaid PbTiO 3 toward the cube diagonal, thus giving rise to a new monoclinic phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epitaxial orientation, as an alternative control parameter in heterostructure customization, has recently attracted rising interests for ferroelectric phase and domain design. [ 17–19 ] Several studies have revealed that the (111) orientation of a cubic substrate can introduce new types of phase instability and structure competition in a tetragonal ferroelectric via a dissimilar surface symmetry element, which we term epitaxial symmetry engineering. For example, unlike the commonly observed tetragonal phase in (001)‐oriented PbTiO 3 film, a SrTiO 3 (111) substrate tends to drive the polarization of overlaid PbTiO 3 toward the cube diagonal, thus giving rise to a new monoclinic phase.…”
Section: Introductionmentioning
confidence: 99%
“…By the same token, lamellar twinned nanodomain (around 40 nm) structures composed of three tetragonal variants can form in (111)‐oriented PbZr 0.2 Ti 0.8 O 3 films. [ 18 ] The complex domain structures contain rich elastic and electrostatic interactions, leading to unusual ferroelastic domain switching. [ 19 ] However, these reported ferroelectric systems via epitaxial symmetry engineering contain only single structural phase, which poses restriction for accessible polarization directions.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the P–V characteristic being a dynamic measurement observed with a 100 Hz triangle wave, whereas the transfer characteristic is a quasi-static measurement. As the time of the application of a voltage higher than the V coer increases, the dipoles become aligned at relatively small voltages [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to nature of ferroelectric materials, of which the polarization is able to be switched in nanosecond order, very recently, their memorizable functions have been characterized in depth as a promising candidate of non-volatile memory generation [1][2][3][4]. In parallel, bismuth ferrite, BiFeO3 (BFO), brings a motivating challenge for ferroelectric memory application, owing to its high remnant polarization [5,6].…”
Section: Introduction mentioning
confidence: 99%